Basic life support: evaluation of learning using simulation and immediate feedback devices - Lucia Tobase; Heloisa Helena Ciqueto Peres; Edenir Aparecida Sartorelli Tomazini; Simone Valentim Teodoro; Meire Bruna Ramos; Thatiane Facholi Polastri (Universidade de São Paulo, 2017)
ABSTRACT Objective: to evaluate students' learning in an online course on basic life support with immediate feedback devices, during a simulation of care during cardiorespiratory arrest. Method: a quasi-experimental study, using a before-and-after design. An online course on basic life support was developed and administered to participants, as an educational intervention. Theoretical learning was evaluated by means of a pre- and post-test and, to verify the practice, simulation with immediate feedback devices was used. Results: there were 62 participants, 87% female, 90% in the first and second year of college, with a mean age of 21.47 (standard deviation 2.39). With a 95% confidence level, the mean scores in the pre-test were 6.4 (standard deviation 1.61), and 9.3 in the post-test (standard deviation 0.82, p <0.001); in practice, 9.1 (standard deviation 0.95) with performance equivalent to basic cardiopulmonary resuscitation, according to the feedback device; 43.7 (standard deviation 26.86) mean duration of the compression cycle by second of 20.5 (standard deviation 9.47); number of compressions 167.2 (standard deviation 57.06); depth of compressions of 48.1 millimeter (standard deviation 10.49); volume of ventilation 742.7 (standard deviation 301.12); flow fraction percentage of 40.3 (standard deviation 10.03). Conclusion: the online course contributed to learning of basic life support. In view of the need for technological innovations in teaching and systematization of cardiopulmonary resuscitation, simulation and feedback devices are resources that favor learning and performance awareness in performing the maneuvers.